Complications in Outpatient Dental Practice - Parry, Nicola (MD Conference Express, 2014)
This article discusses some complications that may be encountered in outpatient dental practice, as well as methods by which to avoid and manage them. Specific highlights include complications in outpatient dental practice are important to consider for various reasons, such as their associated medicolegal implications and potential loss of revenue, and described some of the most common types of complications that can occur.